2002
DOI: 10.1046/j.1464-410x.2002.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

Does smoking status influence the prognosis of bladder cancer? A systematic review

Abstract: Objectives To summarize, in a systematic review, the evidence for the effect of stopping smoking on recurrence, cancer-specific and all cause-mortality among smokers with newly diagnosed bladder cancer. Materials and methods Two electronic databases and the reference lists of identified primary studies and reviews were searched. Studies were included if a hazard ratio and its confidence intervals could be extracted. A predefined set of study characteristics was extracted which defined whether studies were givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
3
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 36 publications
4
59
3
3
Order By: Relevance
“…Although cigarette smoking is considered an established risk factor for the development of bladder cancer, 38 there has been no strong evidence on the effects of smoking on bladder cancer prognosis until recently. 39 The studies were well designed, with a large number of subjects and detailed recording of smoking status, including intensity and duration of smoking. Long-term heavy smokers with primary or recurrent urinary bladder cancer had the worst outcomes, a finding that emphasizes the necessity for smoking cessation counseling in urological patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although cigarette smoking is considered an established risk factor for the development of bladder cancer, 38 there has been no strong evidence on the effects of smoking on bladder cancer prognosis until recently. 39 The studies were well designed, with a large number of subjects and detailed recording of smoking status, including intensity and duration of smoking. Long-term heavy smokers with primary or recurrent urinary bladder cancer had the worst outcomes, a finding that emphasizes the necessity for smoking cessation counseling in urological patients.…”
Section: Discussionmentioning
confidence: 99%
“…Todavia, estudos demonstram que menos de metade dos doentes oncológicos fumadores ao diagnóstico se mantêm abstinentes. [32][33][34][35] Em trabalhos com CB, Vilensku et al 22 e Bassett et al 7 obtiveram 42% e 48% de abstinência após o diagnóstico. Neste estudo, e em linha com a alta prevalência, apenas 40,7% dos fumadores ao diagnóstico abandonaram o consumo, uma percentagem baixa que parece indicar que este teachable moment não está a ser adequadamente aproveitado, tanto pelos doentes na mudança de hábitos, como pelos médicos para uma atuação mais incisiva.…”
Section: Discussionunclassified
“…A recent systematic review concluded that cigarette smoking might be a weak factor influencing prognosis, but the results were inconclusive. 18 Some researchers have investigated the molecular and genetic differences among age groups; however, data are lacking with which to evaluate our hypothesis. Linn et al 19 studied genetic alterations in bladder cancer samples from patients Ͻ30 years and reported frequent p53 gene overexpression.…”
Section: Commentmentioning
confidence: 99%